Nośność graniczna powłoki walcowej obciążonej liniowo-zmiennym ciśnieniem i silą osiową - Wojewódzki, W.; Stolarski, H. (Engineering Transactions, 1969)
The problem solved in the present paper is that of the limit load of a cylindrical shell with clamped edges, subject to the action of a linearly variable pressure and an axial force. The yield surface used is the surface described in Ref. 2, and derived on the grounds of the Tresca yield criterion for a layered wall. Three cases are considered, corresponding to three variability regions of the axial force f. These are -1 < f < -1/2 and 1/2 < f < 1, f= +/-1, -1/2 <f <0 and 0 < f < 1/2. The conditions of static and kinematic admissibility of the solution are established. Other subjects of the discussion are the role of the parameter w characterizing the geometrical form of the shell and the influence of the non-uniformity of the load on the. accuracy of the curves of limit load obtained. Numerical examples are given for f = 0 and ω = 1 in order to illustrate the computation procedure and the way in which the region containing the accurate curve of limit load can be reduced.